Pengaruh Gaya Kepemimpinan Trasformasional, Iklim Sekolah, Motivasi Kerja, Etos Kerja Terhadap Komitmen Organisasional Guru di Sekolah Dasar Gugus R.A. Kartini Kota Denpasar Tahun 2022 - I Nyoman Werna; I Putu Wisna Ariawan; I Made Yudana (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to obtain certainty of simultaneous data on the magnitude of the influence of the principal's leadership style, work climate, work motivation, and teacher work ethic, on the organizational commitment of elementary school teachers at Guus RA Kartini in Denpasar City. This type of research is "ex post facto. The population in this study were all elementary school teachers of the RA Kartini Cluster in Denpasar City, totaling 212 people. Sampling using the solvency formula and taken randomly as many as 140 respondents. Methods of data collection using questionnaires and document studies. The collected data were analyzed by multiple linear analyses with Partial Correlation Analysis. The results showed (1) there was a significant effect of Transformational Leadership Style on Elementary School Organizational Commitment with a correlation coefficient of 0.75% and an effective and relative contribution of 15.98% and 20.03%. (2) There was no significant effect of school climate on organizational commitment with a correlation coefficient of 0.11% and an effective and relative contribution of 08.66% and 10.86% (3). Work motivation has a significant effect on school organizational commitment with a correlation coefficient of 0.33 and an effective and relative contribution of 27.40% and 34.77%. (4) There is a significant effect of the teacher's work ethic on school organizational commitment with a correlation coefficient of 0.35% and an effective and relative contribution of 27.74 and 34.77%. (5) There is a significant simultaneous effect of the principal's Transformational Leadership, Work Climate, Work Motivation, and Work Ethics with a significance level of 0.00 (0.00 <0.05) and a practical contribution of 79.79% to school organizational commitment in the RA Kartini Cluster, West Denpasar District, Denpasar City Education Office.